Physiological roles and diseases of tmem16/anoctamin proteins: are they all chloride channels? - Duran Charity; Hartzell H Criss (Acta Pharmacologica Sinica, 2016)
The Tmem16 gene family was first identified by bioinformatic analysis in 2004. In 2008, it was shown independently by 3 laboratories that the first two members (Tmem16A and Tmem16B) of this 10-gene family are Ca2+-activated Cl− channels. Because these proteins are thought to have 8 transmembrane domains and be anion-selective channels, the alternative name, Anoctamin (anion and octa=8), has been proposed. However, it remains unclear whether all members of this family are, in fact, anion channels or have the same 8-transmembrane domain topology. Since 2008, there have been nearly 100 papers published on this gene family. The excitement about Tmem16 proteins has been enhanced by the finding that Ano1 has been linked to cancer, mutations in Ano5 are linked to several forms of muscular dystrophy (LGMDL2 and MMD-3), mutations in Ano10 are linked to autosomal recessive spinocerebellar ataxia, and mutations in Ano6 are linked to Scott syndrome, a rare bleeding disorder. Here we review some of the recent developments in understanding the physiology and structure-function of the Tmem16 gene family.